Analisis Pengaruh Mitigasi Risiko Likuiditas dan Penyaluran Kredit terhadap Pertumbuhan Ekonomi dan Stabilitas Harga Indonesia Tahun 2010.1 – 2019.4 - M. Naufal Qinthara; Nugroho SBM (Universitas Diponegoro, 2021)
This study aims to analyse the transmition nonetary policies are able to encourage the economy and how their effects on price stability in the short and long term. This study uses secondary time series data of mitigating the risk of liquidity, credit, GDP, and inflation of Indonesia from 2010Q1 to 2019Q4. The hypothesis testing of this research used the Vector Error Correction Model. Based on the results of the VECM estimation, there is a negative and significant relationship between the Secondary Reserve Requirement on GDP. However, the interbank money market variable has a positive effect on GDP in the long run. The volume of bank lending has a positive effect on GDP, but can turn around to be negative in the long run. In addition, with inflation as the dependent variable, the Rupiah interbank money market has a negative and significant effect on inflation in the short and long term. the interbank foreign exchange money market has a positive relationship to inflation in the long run and the level of bank lending has a positive effect on inflation in the short and long term.